2008
DOI: 10.1254/jphs.08203fp
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Chalcone Polyphenol Inhibits the Deacetylase Activity of SIRT1 and Cell Growth in HEK293T Cells

Abstract: Abstract. SIRT1 is one of seven mammalian orthologs of yeast silent information regulator 2 (Sir2), and it functions as a nicotinamide adenine dinucleotide (NAD)-dependent deacetylase. Recently, resveratrol and its analogues, which are polyphenols, have been reported to activate the deacetylase activity of SIRT1 in an in vitro assay and to expand the life-span of several species through Sir2 and the orthologs. To find activators or inhibitors to SIRT1, we examined thirty-six polyphenols, including stilbenes, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 39 publications
0
26
0
Order By: Relevance
“…In endothelial cells, up-regulation of eNOS mRNA by treatment with resveratrol is prevented by knockdown of SIRT1 [37]. Piceatannol and resveratrol activate the deacetylase activity of SIRT1, and the effect of piceatannol is reported to be higher than that of resveratrol [38]. Strong up-regulation of eNOS mRNA by piceatannol is considered to be partly due to the activation of SIRT1.…”
Section: Discussionmentioning
confidence: 99%
“…In endothelial cells, up-regulation of eNOS mRNA by treatment with resveratrol is prevented by knockdown of SIRT1 [37]. Piceatannol and resveratrol activate the deacetylase activity of SIRT1, and the effect of piceatannol is reported to be higher than that of resveratrol [38]. Strong up-regulation of eNOS mRNA by piceatannol is considered to be partly due to the activation of SIRT1.…”
Section: Discussionmentioning
confidence: 99%
“…3,2 0 ,3 0 ,4 0 -tetrahydroxychalcone is a polyphenol identified as an inhibitor of purified SirT1's ability to deacetylate recombinant p53 and a p53 derived peptide (Kahyo et al 2008). In cells, this agent suppressed the cell growth, induced the hyperacetylation of endogenous p53 and increased endogenous p21 CIP1/WAF1 expression.…”
Section: P53-based Cancer Therapymentioning
confidence: 99%
“…It could be suggested that, unlike the rhuschalcones, both C-C and C-O linked non-symmetrical bichalcones be also be synthesized tested against the sirtuins, with the view of investigating potential selectivities against the isoforms. Besides, chalcones have previously shown deacetylase inhibitory properties against sirt1 and cell growth in HEK293T cells [53]. In order to rationalize the interaction of the identified hits in our study, all docking poses for sirt1 (PDB ID: 4ZZJ) and sirt2 (PDB ID: 4R8M and PDB ID: 5D7P) were analyzed using the MOE program [54].…”
Section: Discussionmentioning
confidence: 99%